Assessing the Safety and Efficacy of Thoracoscopic Lung Biopsy in Patients with Interstitial Lung Disease - Mohamed Mustafa Elsheikh (Al-Azhar University, Faculty of Medicine (Damietta), 2021)
Background: Interstitial lung disease [ILD] is a difficult-to-treat disease. The patient continues treatment for his/her whole life. However, certain causes – when diagnosed - could change their treatment plan. Radiological investigations cannot elicit the underlying pathology 100%. Thus, transthoracic lung biopsy is of utmost importance, especially in undiagnosed patients. But, it is not free of risk, and thus, its use is still controversial.Aim of the work: This work aims to evaluate the role of medical thoracoscopic lung biopsy [TLB] in diagnosing diffuse parenchymal lung diseases.Patients and Methods: Fifty patients with diffuse lung infiltrate on high-resolution computed tomography [HCRT] of unconfirmed diagnosis were included. All patients have been submitted to detailed clinical examination and specific laboratory investigations. Furthermore, all had high resolution computed tomography, pulmonary function tests], echocardiography, arterial blood gas analysis, and bronchoalveolar lavage assessment. The thoracoscopic lung biopsy was performed under local anesthesia. The specimens were preserved in formalin containing cups till examination. Patients were followed up, and any complications were documented.Results: The lung HCRT revealed ground-glass opacity [44%], reticulonodular interstitial pattern [38%], honeycombing [14%], crazy paving [10.0%], and consolidation [20.0%]. The histopathology revealed alveolar proteinosis [2.0%], alveolar hemosidrosis [2.0%], hypersensitivity pneumonitis [24.0%], sarcoidosis [8.0%], nonspecific interstitial pneumonia [20%], Idiopathic pulmonary fibrosis [12.0%], respiratory bronchiolitis ILD [18%], and desquamative ILD [14.0%]. All patients positive on HCRT had pathological change. Complications were [12%] bulla in partnehymea, [4%] plural disear, [2%] pneumothorax, and 2% died during follow up duration.Conclusion: TLB is an effective and relatively safe, minimally invasive intervention for interstitial lung disease diagnosis. Accordingly, it must be considered a standard diagnostic tool for undiagnosed suspected cases.